Targeting intestinal flora and its metabolism to explore the laxative effects of rhubarb - Yang, Lei; Wan, Yue; Li, Wenwen; Liu, Chen; Li, Hui-fang; Dong, Zhiling; Zhu, Ke; Jiang, Shu; Shang, Erxin; Qian, Dawei; Duan, Jinao (Applied microbiology and biotechnology, 2022)
Rhubarb, a traditional herb, has been used in clinical practice for hundreds of years to cure constipation, but its mechanism is still not clear enough. Currently, growing evidence suggests that intestinal flora might be a potential target for the treatment of constipation. Thus, the aim of this study was to clarify the laxative effect of rhubarb via systematically analyzing the metagenome and metabolome of the gut microbiota. In this study, the laxative effects of rhubarb were investigated by loperamide-induced constipation in rats. The gut microbiota was determined by high-throughput sequencing of 16S rRNA gene. Ultra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry was used for fecal metabolomics analysis. The data showed that rhubarb could significantly shorten gastrointestinal transit time, increase fecal water content and defecation frequency, improve gastrointestinal hormone disruption, and protect the colon mucus layer. Analysis of 16S rRNA gene sequencing indicated that rhubarb could improve the disorder of intestinal microbiota in constipated rats. For example, beneficial bacteria such as Ligilactobacillus , Limosilalactobacillus , and Prevotellaceae UCG-001 were remarkably increased, and pathogens such as Escherichia-Shigella were significantly decreased after rhubarb treatment. Additionally, the fecal metabolic profiles of constipated rats were improved by rhubarb. After rhubarb treatment, metabolites such as chenodeoxycholic acid, cholic acid, prostaglandin F2α, and α-linolenic acid were markedly increased in constipation rats; in contrast, the metabolites such as lithocholic acid, calcidiol, and 10-hydroxystearic acid were notably reduced in constipation rats. Moreover, correlation analysis indicated a close relationship between intestinal flora, fecal metabolites, and biochemical indices associated with constipation. In conclusion, the amelioration of rhubarb in constipation might modulate the intestinal microflora and its metabolism. Moreover, the application of fecal metabolomics could provide a new strategy to uncover the mechanism of herbal medicines. Key points • Rhubarb could significantly improve gut microbiota disorder in constipation rats. • Rhubarb could markedly modulate the fecal metabolite profile of constipated rats.